Phase-field-model-based analysis of the effects of powder particle on porosities and densities in selective laser sintering additive manufacturing. (15th January 2020) - Zhang, Z.; Yao, X.X.; Ge, P.
Highlights: Internal relations between the powder features and the quality of SLS AM products. The mechanism on controlling of the porosities and densities. Phase field model with combination of process model for the sintering simulation. Abstract: Powder particle features are the key factor for determining the final quality of selective laser sintering (SLS) additive manufacturing products. Different powder particle features, including particle size and distribution, need to be considered. A phase-field model combined with a moving heat source model was used to study the effects of particle features on the porosities and densities of SLS products. The models were validated through comparison with experimental sintering observations. The mechanism of controlling the porosities and densities was explained by simulation. Results indicate that the initial states of powder spreading are a key factor for the changes of porosity and density in SLS additive manufacturing. It is found that smaller powder particles can lead to higher material transportation ratios, which is the reason for higher density and lower porosity when smaller particles are mixed into the powder.